Turning Challenges into Opportunities Through Women Empowerment: Agritourism in Central Luzon, Philippines - Mark Chris M. Lapuz; Christopher R. Manlapaz; Jerry Gil B. Francisco (SAGE Open)
Women are exposed to various challenges, especially when engaged in men’s work. This study described the condition of women as they turned challenges into opportunities in agritourism through women’s empowerment. It was anchored on the theoretical foundations of organizational resilience and women in the tourism framework. The study addressed the key question of how women in agritourism sites of Central Luzon turned the challenges they experienced into opportunities through women empowerment. The research gap bridged by the study involved analyzing the conversion process of challenges into opportunities by validating the presence of different aspects of empowerment in agritourism operations. Qualitative data were gathered through semi-structured interviews among empowered women leaders in agritourism enterprises. Data were analyzed and presented through thematic outcome-pair matching to verify propositions from related literature and studies. Results showed a complete match with the conversion of challenges into opportunities through empowerment in terms of political, economic, and socio-cultural aspects, but a partial match was observed in terms of the physical aspect of empowerment. The study revealed that women in agritourism converted their challenges into opportunities that benefit them as women who excelled in male-dominated industries. Practical implications were observed as agritourism served as a platform for improving the quality of life of women in Central Luzon. The research also contributed to widening the importance of women’s empowerment as a mechanism rather than an end goal in attaining the opportunities offered for women leaders in the agritourism industry.